Meninggalkan Salat Berjemaah Tanpa Uzur Menurut Perspektif Mazhab Syafii dan Mazhab Hambali - Irman Irman; Muhammad Shiddiq Abdillah; Awal Rifai (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to find out what the law is for leaving congregational prayers without delay according to the perspective of the Syafii school of thought and the Hambali school of thought. The problems that researchers raise in this research are: First, what is the position of congregational prayer in Islam. Second, what is the law regarding leaving congregational prayers without delay according to the Syafii school of thought and the Hambali school of thought. This research is library research. This research uses a type of qualitative descriptive research (non-statistical), which focuses on the study of manuscripts and texts, using normative and comparative approach methods. The results of the research show that congregational prayer has an important position and role in Islam, congregational prayer can strengthen the bonds of brotherhood among Muslims. Apart from that, congregational prayer also has many virtues and wisdom, congregational prayer is twenty-five to twenty-seven degrees more important than praying alone. According to the Syafii school of thought, there are three opinions regarding the law of congregational prayer, some are of the opinion that it is sunnah muakadah, some are of the opinion that it is fardu kifayah and there are others that are of the opinion that the law is fardu ain, but the most valid in the Syafii school of thought is the law of fardu kifayah, while the Hambali school of thought is of the opinion that the law is fardu ain. The Syafii school of thought is of the opinion that it is not permissible to leave congregational prayers without a reason, and they are of the opinion that the prayer of someone who prays alone but in congregation is better. Meanwhile, the Hambali school of thought has different opinions regarding the law of leaving congregational prayers, the first opinion says the prayer is invalid while the second opinion says the prayer is valid but one is guilty of leaving the obligation, namely congregational prayer. It is hoped that the implications of this research will provide scientific insight and become a reference on the legal issue of leaving congregational prayers without delay.